Interaction of Environmental Uncertainty, Characteristics of Management Accounting Information Systems and Decentralization on Managerial Performance - Adam Nur Firdausy; Elvin Bastian; Fara Fitriyani (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to examine the effect of the characteristics of management accounting information systems and decentralization on managerial performance with environmental uncertainty as a moderating variable. This research is a type of quantitative research, the data used using primary data and data collection using a questionnaire to obtain information from respondents, namely middle managers who work in manufacturing companies in the feedmill sector in Banten Province. The analytical method used is Structural Equation Model (SEM) with Partial Least Square (PLS) Path Modeling with SmartPLS 3.0 analysis tool. The results of this study are 1) The effect of the characteristics of the management accounting information system on managerial performance, a) Broadscope has an effect on managerial performance, b) Timeliness has no effect on managerial performance, c) Aggregation has no effect on managerial performance, d) Integration has no effect on managerial performance, 2) Decentralization has an effect on managerial performance, 3) The effect of environmental uncertainty moderates the relationship between the characteristics of management accounting information systems on managerial performance, a) Environmental uncertainty does not moderate the relationship between broad- scope management accounting information characteristics and managerial performance, b) Environmental uncertainty does not moderate the relationship between characteristics of management accounting information timeliness with managerial performance, c) Environmental uncertainty does not moderate the relationship between the characteristics of aggregation management accounting information with managerial performance, d) Uncertainty environmental assurance does not moderate the relationship between the characteristics of integrated management accounting information and managerial performance, 4) Environmental uncertainty moderates the relationship between decentralization and managerial performance